(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The present study was designed to study teleconferencing as a technique of learning at postgraduate level of IGNOU students. In order to study this, a self made questionnaire was made and assignments were given to the students. The questionnaire contained 50 questions covering 7 aspects of teleconferencing session being held. These aspects were- perception of students, content and presentation, program design related issues, interaction aspect, effectiveness, flexibility and appropriateness. Secondly, the investigator evaluated the difference in learning on the basis of marks obtained in assignments by participants and non participants of postgraduate level. Sample of 200 students of post graduate level of IGNOU were taken. Study centers and regional centers with the provision of video teleconferencing were taken. Relevant means, S.Ds, t values were calculated to draw the conclusions. On the basis of it can be concluded that teleconferencing is an effective technique for learning.